The Murder of Queen Elizabeth – a Case Study of the Late Medieval Political Propaganda - Ančić, Mladen (ASPICE HUNC OPUS MIRUM: zbornik povodom sedamdesetog rođendana Nikole Jakšića, 2020)
The paper is focused on the question whether the Queen Regent Elizabeth was murdered or died of natural causes during her imprisonment in January, 1387. In order to resolve ambiguities the author analyzes content of the narratio formula of the royal charter issued in the name of the Queen Mary on September 14, 1387, as well as contemporaneous literary texts – poem Carmen de Carolo Parvo written by Lawrence de Monacis and “diary-chronicle” of the Zadar patrician Paul de Paulo. After the thorough analysis the author concludes that different versions of the stories concerning the capture and imprisonment of the Queens Elizabeth and Mary were produced as a political propaganda serving the interests of two confronted political factions that formed the ruling stratum of the Kingdom of Hungary-Croatia.